2001
DOI: 10.1007/s004410000279
|View full text |Cite
|
Sign up to set email alerts
|

Putative role of basement membrane for dentinogenesis in the mesenchyme of murine dental papillae in vitro

Abstract: In a new culture-conditioning system of agar-coated mesenchyme of isolated incisor dental papillae, dentinogenesis has been induced adjacent to an agar substratum that functions as a foothold for cell immobilisation. To elucidate the role of the basement membrane (BM) in dentinogenesis, we have examined the way in which dentinogenesis depends upon BM components or transforming growth factor (TGF)-beta1 in this system. At the mesenchymal-epithelial junction of odontogenic organs (cut incisor tooth germs), TGF-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 71 publications
(104 reference statements)
0
16
0
Order By: Relevance
“…They were pre-coated with 2.0 mg/ml bovine type I collagen (Koken Co., Tokyo, Japan) mixed with 1.0 mg/ml mouse EHS laminin (Harbor Bio-products, Norwood, MA, USA). They were then coated with a 1.5% agar (Wako) solution (Kikuchi et al 2001). The agar blocks were incubated for 8 days in the same DMEM as described above.…”
Section: Microinjection and Organ Culturementioning
confidence: 99%
See 3 more Smart Citations
“…They were pre-coated with 2.0 mg/ml bovine type I collagen (Koken Co., Tokyo, Japan) mixed with 1.0 mg/ml mouse EHS laminin (Harbor Bio-products, Norwood, MA, USA). They were then coated with a 1.5% agar (Wako) solution (Kikuchi et al 2001). The agar blocks were incubated for 8 days in the same DMEM as described above.…”
Section: Microinjection and Organ Culturementioning
confidence: 99%
“…Under experimental conditions, dentinogenesis can be induced by members of the transforming growth factor-尾 (TGF-尾) superfamily combined with certain growth factors (Ruch et al 1995), and is induced adjacent to the structural surface of an ECM-absorbed agar substratum (Kikuchi et al 1996(Kikuchi et al , 2001. It can also be induced adjacent to artificial ECM or hydroxyapatite/tricalcium phosphate in grafts (Tziafas et al 1995;Gronthos et al 2000Gronthos et al , 2002.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The understanding that dentinogenesis can be induced by dental papilla under the effect of some growth factors like TGF-b or by contacting with Annexin v assay (c) and quantitative analysis (d) suggested that there were constitutively more numerous apoptotic cells in ADAM28 AS-ODN group specific extracellular matrix (ECM) substratum reveals remarkable new insights that hDPMCs may feature characteristics shared by putative progenitor cells/stem cells for dentin formation (Ruch et al 1995;Kikuchi et al 1996Kikuchi et al , 2001. The course of hDPMCs differentiation is synergistically or antagonistically modulated by sequential and interdependent transcription factors and accompanies the expression of corresponding markers.…”
Section: Discussionmentioning
confidence: 99%